EVALUATION OF LDL-CHOLESTEROL & HDL-CHOLESTEROL, IN FEMALE HYPOTHYROID PATIENTS OF AGE 20-50 YEARS - Muhammad Shahzad Farooq; Bushra Shaheen; Iram Qamar (Journal of University Medical & Dental College, 2015)
ABSTRACT: OBJECTIVE: The aim of this study was to observe the effects of hypothyroidism on lipoprotein with special reference to LDL-C and HDL-C. We also evaluated the correlation of TSH, FT4 & FT3 with LDLC and HDL-C. STUDY DESIGN: It is analytical cohort type study. PERIOD OF STUDY: This study was conducted from March 2011 to January 2012. (Ten months) Setting : Punjab Institute of Nuclear Medicine (PINUM), Faisalabad and University of Lahore. METHODS: The overall 120 female patients of age 20-50 years were investigated for FT3, FT4, TSH, HDLC and LDL-C. Among these 100 patients were of hypothyroidism and 20 euthyroid subject for control. RESULT : The LDL-Cholesterol in hypothyroid patients was significantly higher than euthyroid subjects. The significant positive correlation was observed between TSH levels and LDL-C. The significant negative correlation was found between serum FT4 and LDL-C. The HDL-C increased insignificantly. CONCLUSION: There is increase LDL-C levels in hypothyroid patients. This may contribute to atherosclerotic coronary artery disease.